2016
DOI: 10.1097/md.0000000000004674
|View full text |Cite
|
Sign up to set email alerts
|

Distraction osteogenesis as a treatment of obstructive sleep apnea syndrome

Abstract: Background:To conduct a systematic review to answer the clinical question “What are the effectiveness of mandibular distraction osteogenesis (MDO) and its complications to treat patients with obstructive sleep apnea syndrome (OSAS)?”.Methods:A systematic search including a computer search with specific keywords, reference list search, and manual search were done. Relevant articles on MDO were assessed and selected in 3 rounds for final review based on 5 predefined inclusion criteria and followed by a round of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 138 publications
0
10
0
Order By: Relevance
“…Because of the traction of the surrounding soft tissues, the advancement of the conventional orthognathic surgery is limited, the potential risk of bone recurrence would be increased along with larger mandibular advancement. However, comparing with sagittal split ramus osteotomy (SSRO), DO had a high major complication rate [ 16 ], ranged from 0% to 21.4%, most were local wound infection or neurosensory disturbance [ 17 ]. It was encouraging that out of the previously reported cases, the large majority were resolved with antibiotics, time and steroids [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the traction of the surrounding soft tissues, the advancement of the conventional orthognathic surgery is limited, the potential risk of bone recurrence would be increased along with larger mandibular advancement. However, comparing with sagittal split ramus osteotomy (SSRO), DO had a high major complication rate [ 16 ], ranged from 0% to 21.4%, most were local wound infection or neurosensory disturbance [ 17 ]. It was encouraging that out of the previously reported cases, the large majority were resolved with antibiotics, time and steroids [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review in 2016 by Tsui et al concluded 100% success rate and 82-100% cure rate for adult OSA patients treated with DO (61). Paediatric OSA patients had a success rate of 90-100%.…”
Section: Domentioning
confidence: 99%
“…Reported complications include infections around the distraction rods, temporary facial nerve palsy, neurosensory disturbances at lower lip and chin areas, anterior open bite, and mechanical failure of distractor. Post-operative tracheostomy was indicated in one child and one death was recorded (61). It is noteworthy that a randomized control trial comparing mandibular DO and bilateral sagittal split osteotomies in nonsyndromic adult OSA patients was terminated early due to major complications in the mandibular DO group (63).…”
Section: Domentioning
confidence: 99%
“…The success rate of decannulation after mandibular distraction osteogenesis may be lower in patients with craniofacial microsomia compared to other craniofacial syndromes including Pierre Robin sequence or Treacher Collins syndrome (reported in a single study including 62 patients (7 with CFM) in the tracheostomy first group; OR 0.05, CI 0.005-0.43). Ref (17,18,37,(39)(40)(41)44)…”
Section: Levelmentioning
confidence: 99%